Framing transitions in a positive light. (2nd May 2019) - Thomas, Beth
Abstract : It is only by grasping the context of children's transitions that we can begin to understand how they might experience changes in their life. To support the child, practitioners must prioritise on communication while also being responsive to what they may be unable to express.